Indução de tolerância à injuria do frio em banana pela aplicação do tratamento hidrotérmico e ácido salicílico - Araújo, Nícolas Oliveira de (Universidade Federal Rural do Semi-Árido, 2017)
The experiment was conducted aiming to evaluate the influence of hot water treatment e of salicylic acid on reducing chilling injury symptoms in banana harvested at different stages of development. Banana fruits harvested within 11 to 13 weeks after unfolding of flower (WUF) were immersed in water at 49±1°C for 10 minutes, in salicylic acid (1.5mM) for 10 minutes and in water at room temperature (control), and posteriorly stored for three to eight days at 6°C. After each period of refrigerated storage, fruits were transferred to room temperature (22°C) to simulate the shelf lifeand immersed in 1500ppm ethephon solution to induce ripening. After eight days of storage at 6°C plus four days at 22°C, the accumulation of soluble solids (SS) of fruits of 13 SEI undergone through control and treatment with salicylic acid was lower than the SS accumulation in fruits of 13 SEI undergone through the hot water treatment. Total phenolic content did not present a clear relation with the levels of chilling injury in banana. Increase in exposition time from three to eight days at 6°C increased chilling injury rate during the shelf life. Generally, fruits of 13 SEI presented more sensible to cold temperatures, exhibiting higher values of chilling injury rate. The hot water treatment reduced the symptoms of chilling injury, however its efficiency in increasing the fruit’s tolerance to cold was temporary, being less efficient in fruits stored for eight days at 6°C and four days at 22°C. The increase of exposition time to cold temperatures increased CO2production after the transfer to room temperature of fruits with 11 SEI, on the other side, the respiration of fruits harvested with 13 SEI drastically decreased in room temperature after eight days of refrigerated storage, except for fruits undergone through the hot water treatment. The hot water treatment reduced the sensibility of cell membrane, evidenced by the lower percentage of electrolytes leakage
Monografia
Keywords: Armazenamento refrigerado; Permeabilidade de membrana; Tempo de prateleira; Fenólicos totais; Refrigerated storage; Membrane permeability; Shelf life; Total phenolics; CIENCIAS AGRARIAS::AGRONOMIA